1H-NMR and viscosity studies of hydrogen bonding of Chinese rice wine. Issue 1 (1st January 2018) - Cao, Jingjing; Liu, Kun; Zhang, Aona; Yan, Wanghui; Zheng, Yue; Zeng, Qingmei
ABSTRACT: The viscosity of Chinese rice wine gradually increases with the maturing process, resulting in a better taste due to longer contact with the tongue. Herein, the structure of water–ethanol was detected by hydrogen nuclear magnetic resonance ( 1 H-NMR) and viscosity measurement to define the strength of hydrogen bonding. Through single-factor experiments, it can be seen that most of the flavors have a promoting effect on alcohol–water hydrogen bonding, with the exception of aldehydes. And the factors influencing hydrogen bonding in decreasing order were determined by Plackett–Burman (PB) test. The relationship between hydrogen bonding strength and flavor in Chinese rice wine with 18% (v/v) alcohol concentration was investigated through multiple regression analysis, with an adjusted R 2 of 0.925. The results of study provide important insight for the quality control and molecular mechanism of viscosity increasing during Chinese rice wine aging.